El entenado de Juan José Saer, mito, islas y límites - Blay Chavez, Maria Elena (Romanica Silesiana)
A cabin boy arrives with his crew to the territory of the Rio de la Plata. Saer was inspired by the story of Francisco del Puerto, a ship’s boy who travelled with the expedition of Juan Diaz de Solís that allegedly ended up eaten by a cannibalistic tribe of one of the islands of Parana’s delta. The hero is bound to learn from the new territory two times; but it is the search for identity, the narration to preserve memory, the construction of the general history, and the limits of one’s self that this article deals with. Key words: Island, tribe, language, identity, memory, otherness